2004
DOI: 10.2337/diacare.27.10.2568
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence of Diabetes: Estimates for the Year 2000 and Projections for 2030

Abstract: Associations between the characteristics of general practitioners and their patients with type 2 diabetes O besity is an important cardiovascular risk factor in type 2 diabetes (1). Physician characteristics such as age and sex are related to counseling for overweight (2). Other physician characteristics may also be related. Patients indicated greater confidence in nonobese versus obese physicians. Whether this translates into increased success in obesity management is unknown (3). We aimed to study associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
203
0
15

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(231 citation statements)
references
References 4 publications
2
203
0
15
Order By: Relevance
“…The World Health Organization (WHO) estimates that there will be more than 550 million cases by 2030. These patients are predisposed to cardiovascular morbidity and mortality (Rathmann & Giani, 2004). Cardiovascular events account for two‐thirds of the mortality in patients with diabetes (Boudina & Abel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) estimates that there will be more than 550 million cases by 2030. These patients are predisposed to cardiovascular morbidity and mortality (Rathmann & Giani, 2004). Cardiovascular events account for two‐thirds of the mortality in patients with diabetes (Boudina & Abel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…No sensitivity analysis was performed for the WHO estimates of diabetes prevalence used for these calculations (6), and we have not speculated on the possible range. However, subsequent studies have shown that the WHO study probably underestimated the prevalence of diabetes (23), and, consequently, these mortality estimates are likely to be conservative.…”
Section: Validationmentioning
confidence: 99%
“…The number of patients with diabetes mellitus (DM), a metabolic disorder, is rapidly increasing worldwide due to several factors: population growth, aging, urbanization, increasing prevalence of obesity and reduced physical activity [ 1 ] . Increased oxidative stress (OS) may have an important causal role in β-cell failure and the development of insulin resistance, it is believed to be related with the onset and progression of diabetes.…”
mentioning
confidence: 99%